Dual role of a g-C3N4/carbon intra-Schottky junction in charge carrier generation and separation for efficient solar H2 production. Issue 13 (14th June 2019) - Shaheer, A. R. Mahammed; Karthik, P.; Karthik, G.; Shankar, M. V.; Neppolian, B.
Abstract : Intra-Schottky junction facilitated charge carrier generation and separation in g-C3 N4 for efficient solar H2 production. Abstract : Graphitic carbon nitride (g-C3 N4 ) has been considered as a prominent metal-free visible light-driven photocatalyst for solar water splitting. However, the rapid recombination of photogenerated charge carriers massively limits its photocatalytic performance. Herein, we have constructed an intra-Schottky junction in g-C3 N4 by enriching it with carbon via a solid-state calcination method to improve the charge carrier separation efficiency for solar photocatalytic H2 production. Enriching of carbon in g-C3 N4 led to the effective overlapping between 2p orbitals of both nitrogen and carbon, thereby inducing an intra-Schottky junction by increasing the C/N ratio as confirmed by XPS analysis. Importantly, compared to bare g-C3 N4, ∼6-fold enhancement on the photocatalytic H2 production rate was achieved with 5 wt% carbon enriched g-C3 N4 photocatalyst. The enhanced photocatalytic activity was mainly attributed to efficient charge carrier generation and separation through an intra-Schottky junction as revealed by photoluminescence, photocurrent and impedance studies. Moreover, the C-enriched g-C3 N4 photocatalyst has shown higher photostability and photocatalytic H2 production activity compared to that in previous reports. Thus, we trust that the present study may provide an insight into the fabrication of an intra-heterojunction for enhanced photocatalysis.